2018
DOI: 10.1039/c7ra13650a
|View full text |Cite
|
Sign up to set email alerts
|

Green controllable synthesis of Au–Ag alloy nanoparticles using Chinese wolfberry fruit extract and their tunable photocatalytic activity

Abstract: Au–Ag alloy nanoparticles, synthesized using wolfberry fruit extract, showed linearly tunable photocatalytic activity through changing alloy composition and synthesis parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 46 publications
1
18
0
Order By: Relevance
“…The nanoparticles obtained by green methods have been applied in various fields, such as adsorbant/ antioxidants [162], chemocatalytic reactions [163][164][165][166][167][168][169], oxidative desulfurization [170], dyes degradation [96,[171][172][173][174][175], degradation of organochlorine compounds [176], sensors development [177,178], electrodes development [179,180], antibacterial agents [164,[181][182][183][184][185][186][187][188][189], antiviral agents [190], antifungal agents [191], cytotoxic agents [192,193], larvicidal agents [190,194], photocatalysts [187,[195][196][197], anti-cancer agents [186,189,[198][199][200][201]…”
Section: Applications Of Nanoparticlesmentioning
confidence: 99%
“…The nanoparticles obtained by green methods have been applied in various fields, such as adsorbant/ antioxidants [162], chemocatalytic reactions [163][164][165][166][167][168][169], oxidative desulfurization [170], dyes degradation [96,[171][172][173][174][175], degradation of organochlorine compounds [176], sensors development [177,178], electrodes development [179,180], antibacterial agents [164,[181][182][183][184][185][186][187][188][189], antiviral agents [190], antifungal agents [191], cytotoxic agents [192,193], larvicidal agents [190,194], photocatalysts [187,[195][196][197], anti-cancer agents [186,189,[198][199][200][201]…”
Section: Applications Of Nanoparticlesmentioning
confidence: 99%
“…Monometallic nanoparticles as well as metallic alloy nanoparticles have been manufactured using plant-based approaches. For instance, Ag–Ni, Ag–Co, Pt–Cu, Au–Ag, Ag–Cu, and Zn–Ag nanoparticles have been produced using the leaf extracts of Canna indica , Alchornealaxiflora , Azadirachta indica, Cacumen Platycladi , palm, Mirabilis jalapa, and Moringa oleifera [ 179 , 180 , 181 , 182 , 183 , 184 , 185 ], Au–Ag–Sr, and Fe–Ag–Pt nanoparticles were produced from the roots of coriander, Platycodon grandiflorum [ 13 , 186 ], and Au-Ag nanoparticles have been produced from the Chinese wolfberry fruit extracts [ 187 ].…”
Section: Methods Of Synthesizing Alloy Nanoparticlesmentioning
confidence: 99%
“…The authors revealed only the catalytic properties of the generated NPs and demonstrated the effectiveness of 2,4,6-trinitrophenols for the catalytic destruction. The authors of [9] obtained the bimetallic alloy Ag-Au with the use of fruit extract (Goji berries). The extract was obtained by maceration during boiling.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…However, there is no data on the properties of the obtained materials and an industry for their further practical application. It should also be noted that the authors of other studies [8][9][10] consider only traditional methods, particularly maceration method, for obtaining extracts of the plant material. The main disadvantage of the method is incompleteness of the extraction.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%